2018
DOI: 10.12788/jhm.2898
|View full text |Cite
|
Sign up to set email alerts
|

A Prescription for Note Bloat: An Effective Progress Note Template

Abstract: The bundled intervention for progress notes significantly improved the quality, decreased the length, and resulted in earlier note completion across 4 academic medical centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 24 publications
0
50
1
Order By: Relevance
“…In addition, user composability requires proper training techniques with implementation in order to maximize its potential. 21 Changing the order of the clinical note may also improve usability 18,19 . Putting salient information at the beginning of the note may allow physicians to spend less time searching through extraneous information, and thus reduce the cognitive burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, user composability requires proper training techniques with implementation in order to maximize its potential. 21 Changing the order of the clinical note may also improve usability 18,19 . Putting salient information at the beginning of the note may allow physicians to spend less time searching through extraneous information, and thus reduce the cognitive burden.…”
Section: Discussionmentioning
confidence: 99%
“…Information overload can also be mitigated through educating physicians to write more efficient notes. Kahn et al 19 demonstrated that physicians who undergo a training session and use a template write notes that are 25% shorter and take 1.3 hours less time.…”
Section: The Cognitive Burden Of Information Overloadmentioning
confidence: 99%
“…38 A few studies have attempted educational interventions that successfully have increased the quality of progress notes while decreasing note length. 39,40 These studies show promise, but more direct changes in regulation and EHR design may be desirable in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of our study was comparable with that of prior psychometric validation studies. 33,34 Upon reviewing the A&Ps associated with these admissions, 365 notes were excluded for one of three reasons: (1) the note was written by a nurse practitioner, physician assistant, resident, or medical student; (2) the admission diagnosis had been definitively confirmed in the emergency department (eg, abdominal pain due to diverticulitis seen on CT); and (3) the note represented the fourth or more note by any single provider (to sample notes of many providers, no more than three notes written by any single provider were analyzed). A total of 285 admission notes were ultimately included in the sample.…”
Section: Data Collectionmentioning
confidence: 99%